Eating behavior and weight gain during pregnancy. (January 2020) - Tang, Xuyang; Andres, Aline; West, Delia S.; Lou, Xiangyang; Krukowski, Rebecca A.
Abstract: Objectives: Little is known about the relationship between eating behavior and weight gain during pregnancy. Purpose: Our objective was to assess the relationship among self-reported cognitive restraint, disinhibition, and hunger, and excessive gestational weight gain (GWG) as defined by the Institute of Medicine's (IOM) 2009 guidelines. Based on previous research examining eating behaviors and weight gain in non-pregnant women, we hypothesized that excessive GWG would be related to higher cognitive restraint, higher disinhibition, and higher perception of hunger. Methods: 190 pregnant women from the Glowing study completed the Three-Factor Eating Questionnaire (TFEQ) at the enrollment visit, which included subscales assessing restraint, disinhibition, and hunger. Participants' height and weight from <10 weeks through 36 weeks gestation were measured, allowing classification within or in excess of the IOM guidelines adjusted for the week of the final measurement. Results: The odds that a participant would gain weight above IOM recommendations was 1.2 times higher (OR = 1.17, 95% CI = 1.05–1.29) for each one-unit increase in the disinhibition subscale in the unadjusted logistic regression. However, after controlling for sociodemographic characteristics and baseline BMI categories, participants' TFEQ scores were not associated with the likelihood of having GWG above IOM guidelines. Eating behaviors subscales were modestly correlated with baseline BMI categories (all rs < 0.50 with p-values ranging from <0.001 to 0.619). Conclusions: Although disinhibition scores had a significant relationship with excessive GWG, the significance of this relationship was not sustained after adjusting for sociodemographic characteristics and baseline BMI categories. Highlights: There are few known predictors to identify women at risk for excessive pregnancy weight gain. Eating behavior may be an important predictor of excessive weight gain. Disinhibited eating had a significant relationship with excessive weight gain. After adjusting for baseline factors, disinhibited eating did not predict weight gain. Future studies should examine other behavioral predictors of excessive weight gain.